2020
DOI: 10.1021/acs.jpcc.0c07330
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Synthetic Pathway to Large-Area, High-Quality [AgSePh] Nanocrystal Films

Abstract: Silver benzeneselenolate [AgSePh]∞ is a coordination polymer that hosts a hybrid quantum well structure. The recent advancements in the study of its tightly bound excitons (~300 meV) and photoconductive properties makes it an interesting representative of a material platform that is an environmentally stable alternative to 2D metal halide perovskites in terms of optoelectronic properties. To this aim, several challenges are to be addressed, among which the lack of control over the metal-organic reaction proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…Of the 2D MOCs reported so far, silver phenyl­selenolate (AgSePh) , has received the most attention because of its blue luminescence (Figure a) and in-plane anisotropy, which are attractive features for light-emitting applications and light–matter coupling. AgSePh naturally adopts a multi-quantum-well structure consisting of slabs of silver selenide separated by layers of phenyl rings (Figure b), leading to a high exciton binding energy of ∼400 meV , and a picosecond photoluminescence (PL) lifetime .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 2D MOCs reported so far, silver phenyl­selenolate (AgSePh) , has received the most attention because of its blue luminescence (Figure a) and in-plane anisotropy, which are attractive features for light-emitting applications and light–matter coupling. AgSePh naturally adopts a multi-quantum-well structure consisting of slabs of silver selenide separated by layers of phenyl rings (Figure b), leading to a high exciton binding energy of ∼400 meV , and a picosecond photoluminescence (PL) lifetime .…”
Section: Introductionmentioning
confidence: 99%
“…24 Furthermore, AgSePh can be prepared in different forms, depending on the end use need. For example, AgSePh thin films can be prepared by a scalable vapor-phase chemical transformation, 21,25 and microcrystals can be synthesized by a solution-phase hydrothermal synthesis. 22 However, these methods typically yield small AgSePh crystals with average lateral sizes of <5 μm, making fundamental studies and device integration challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic chalcogenolates (MOCs) of coinage metals are nontoxic covalently bound hybrid organic–inorganic materials with [M­(ER)] n chemical formula, where M = Cu­(I), Ag­(I), Au­(I); E = S, Se, Te; and R is an organic hydrocarbon . Recently, silver phenylselenolate (AgSePh), a 2D member of the broader class of MOC coordination polymers, has gained a renewed interest as a class of hybrid organic–inorganic 2D semiconductors (Figure a). While AgSePh was discovered and its structure refined almost 20 years ago, its semiconducting properties were not realized until 2018. , Recent studies have demonstrated many promising properties of AgSePh such as strong exciton binding energy, , chemical robustness, , nontoxic elemental composition, in-plane anisotropy, and low-cost and scalable synthetic methods. , Moreover, the covalent interaction between organic and inorganic layers potentially provides an opportunity to control the properties of 2D semiconductors through organic functionalization as shown in the thiolate analogues of AgSePh …”
mentioning
confidence: 99%
“…Among the 2D MOCs reported so far, silver phenylselenolate (AgSePh), also known as “mithrene”, has attracted the most attention due to its natural blue (∼467 nm) emission. , It was shown that silver phenyltellurolate (AgTePh), known as “tethrene”, also crystallizes into a 2D structure at room temperature with the same monoclinic centrosymmetric space group C 2/ c as AgSePh. , (Note that AgSePh has also been reported in the P 2 1 / c structure, which is very similar in structure to C 2/ c .) However, AgTePh exhibits a strikingly different optical behavior from AgSePh despite the structural and compositional similarity, implying a different physical mechanism underlying light emission in AgTePh.…”
mentioning
confidence: 99%